2019
DOI: 10.1029/2018je005743
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis and In Situ U‐Pb Geochronology of a Strongly Shocked L‐Melt Rock Northwest Africa 11042

Abstract: Northwest Africa (NWA) 11042, originally classified as a primitive achondrite with no chondritic relicts, is rather a unique L‐melt rock. It is a severely shocked, igneous‐textured ultramafic rock composed of euhedral to subhedral olivine (Fa25.1 ± 0.5) and pyroxenes (low‐Ca pyroxene Fs20.7 ± 0.8Wo4.2 ± 1.0 and Ca‐rich pyroxene Fs11.5 ± 0.5Wo37.6 ± 1.2) with interstitial albitic plagioclase (Ab80.7 ± 1.7Or5.0 ± 0.7) that has been completely converted to maskelynite. Mineral compositions are similar to those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 89 publications
2
27
0
Order By: Relevance
“…Wu and Hsu () recently dated NWA 11042 using phosphate 207 Pb‐ 206 Pb and found disturbed concordance with an upper intercept age of 4479 ± 43 Ma and a lower intercept age of 465 ± 47 Ma. These ages concord with phosphate 207 Pb‐ 206 Pb ages obtained from the L6 chondrite Novato of 4472 ± 31 Ma and 473 ± 38 Ma (Yin et al.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Wu and Hsu () recently dated NWA 11042 using phosphate 207 Pb‐ 206 Pb and found disturbed concordance with an upper intercept age of 4479 ± 43 Ma and a lower intercept age of 465 ± 47 Ma. These ages concord with phosphate 207 Pb‐ 206 Pb ages obtained from the L6 chondrite Novato of 4472 ± 31 Ma and 473 ± 38 Ma (Yin et al.…”
Section: Discussionmentioning
confidence: 92%
“…The younger ages, interpreted as shock resetting ages, agree well with our more precise Ar‐Ar age of 484.0 ± 1.5 Ma. The older age of Wu and Hsu (), interpreted as the crystallization age, argues strongly against petrogenesis by partial differentiation of the L chondrite parent body, since any short‐lived radiogenic heat sources would have decayed away by that time. Instead, Wu and Hsu () suggest that NWA 11042 was formed inside a thick melt dike within a large impact structure which remained thermally insulated for long enough to generate the igneous properties observed in the meteorite.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 shows literature REE patterns of silicates and phosphates from typical equilibrated OCs (Allen & Mason, 1973; Curtis & Schmitt, 1979) as well as H7 Watson 012 (Tait et al, 2014) and L chondrite melt rock NWA 11042 (Wu & Hsu, 2019). In previous studies, the silicate separates from typical equilibrated OCs showed large variations in their REE contents, which could be induced by different degrees of contamination of mineral inclusions with high REE contents.…”
Section: Resultsmentioning
confidence: 99%
“…Early impacts could have produced an order of magnitude more heat than late impact events (Davison et al, 2013). As a consequence, the parent bodies of chondrites likely experienced many collisions, which are recorded as successive episodes of shock metamorphism, melting and annealing in various meteorites (e.g., LL6 MIL 99301, H6/7 Portales Valley, L‐melt rock NWA 11042; Rubin, 2002, Ruzicka & Hugo, 2018, Wu & Hsu, 2019). The meteorites' thermal histories reflect complex interactions involving coincident radiogenic thermal metamorphism (due to 26 Al decay; e.g., McSween et al, 2002) and collisional heating (e.g., Rubin, 1995) on early parent bodies.…”
Section: Introductionmentioning
confidence: 99%
“…This composition also falls on the Mars fractionation line. Past work has shown that shergottite-like textures, mineralogies, and mineral chemistries can be generated from L chondrite melts (Wu and Hsu 2019). The identification of additional sources of basalt generation and the mixing of chemical reservoirs demands that caution be taken when meteorite source locations are studied, particularly for meteorites composed entirely of breccia and impact melt products.…”
Section: The Rim As An Example Of Chemical Mixing By Impact Accretionmentioning
confidence: 99%